Islamic Legal Perspectives on the Practice of Tajdīd al-Nikāḥ within Madurese Tradition: A Case Study in Lantek Barat Village, Indonesia - Mahrus Ali; Shofiatul Jannah; Dzulfikar Rodafi (Bulletin of Indonesian Islamic Studies, 2025)
The socio-religious tradition of Tajdīd al-Nikāḥ is not merely a ritual, but rather a manifestation of administrative needs, spiritual beliefs, and efforts to strengthen the foundations of the household. This study aims to uncover the practice of Tajdīd al-Nikāḥ in the community, explore the motives behind its implementation, examine its impact on social life, and examine it through the perspective of Islamic law. This research is a qualitative study using empirical legal methods with a case study approach. Data collection techniques were carried out through observation, in-depth interviews with community and religious leaders, and documentation. Data analysis was carried out through data condensation, data presentation, and drawing conclusions. The results reveal that Tajdīd al-Nikāḥ in West Lantek Village is practiced by couples who have been married religiously but have not been registered with the Office of Religious Affairs (KUA). Its implementation is driven by administrative needs, strengthening household relations, and local beliefs regarding the blessings of re-wedding contracts. Within the framework of Islamic law, this practice is considered valid as long as it fulfills the pillars and requirements of marriage, and is in line with sharia principles. Analysis based on the Shafi'i School of Law, 'urf, and Maqashid al-Syari'ah shows that Tajdīd marriage can be accepted as a socio-religious mechanism to maintain lineage, family dignity, and societal stability.